I'm so confused how to you solve for the x intercepts in these equations? I couldn't find a way to factor it in a way that makes sense.... x^2-6x+3 and the other equation is 3x^2+2x=x^2+9X-3

3x^2+2x=x^2+9X-3

3x^2-x^2+2x-9X+3=0

2x^2-7x+3=0

2x^2-6x-x+3=0

2x(x-3)-1(x-3) = 0

(x-3) (2x-1) = 0

x-3=0 or 2x-1 = 0

x=3 or 2x=1

x=3 or x=1/2

For this question x^2-6x+3 the information are incomplete.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up